Gambaran Pasien Miopia di Rumah Sakit Mata Bali Mandara Tahun 2022 - Gst Ayu Kade Devina Muryantisa; Putu Nita Cahyawati; I Made Pariartha (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2024)
[Overview of Myopia Patients at Bali Mandara Eye Hospital in 2022] Myopia is the most common abnormal refractive that occurs with a prevalence of myopia in the world of 49.8%, in Indonesia around 25% and in the province of Bali 25%. The results of a survey conducted at the largest eye hospital in Eastern Indonesia, the Bali Mandara Eye Hospital, recorded a fairly high prevalence of myopia, namely 1,418 patients in 2022. This research aims to find out the picture of myopia patients at the Bali Mandara Eye Hospital in 2022. This research uses a descriptive method with a cross sectional approach. The sampling technique used in this research was simple random sampling with a total of 133 respondents. Data were processed using Statistical Product and Service Solution (SPSS) version 23 with univariate analysis. In this study, the description of myopia patients based on sociodemographics was dominated by the age group 12-25 years (41.4%), women (51.9%), students (41.4%), and those live in Bali (95%). Based on clinical symptoms, patients generally present with complaints of blurred vision (89.5%), mild myopia (54.9%) and lateralization in both eyes (83.5%). Based on the history of comorbidities, the results showed that only 2 (1.5%) had a history of diabetes mellitus and only 1 (0.8%) had a history of hypertension. Based on the type of management, the highest number was pharmacological and non-pharmacological management (82.7%).